A global review of pollination syndromes: a response to ollerton et al. 2015 - Aguilar, Ramiro (2015)
In a recent literature review, we demonstrated that the evolution of floral traits is driven by adaptation to the most effective pollinators. In a critique of this study, Ollerton et al. 2015 claimed there were apparent flaws with data collection, analyses and interpretation of results. We disagree since many of OLT´s observations and recommendations are subjective and overlook basic aspects of meta-analysis. Here, we address the main criticisms of Ollerton et al 2015.